Optimising Waqf law for effective administration: a comparative analysis of the Trustee Act 1949 and state Waqf enactments - Abdul Manaf, Zati Ilham; Mohd Najid, Khadijah; Drs Nasrul, Muhammad Amrullah; Muhamad Ibrahim, Najhan (IIUM Press, 2023)
Waqf, an Islamic social finance instrument, can be a tool for sustainable economic development if efficiently managed and optimally implemented. As more states in Malaysia seek to improve the governance and administrative responsibilities of theirWaqf trustees through a regulatory framework, this article aims to propose statutory amendmentsthat emphasise the principles of integrity and fairness in the pursuit of justice, ultimatelyimprovingthe governance and administrative responsibilities of Waqf administrators in Malaysia. Using qualitative and comparative legal analysis, this study compares the duties of trustees under the Trustee Act of 1949 with those of Mutawalliand Nazhirsin selected Waqf enactments to provide insights for perfecting the current Waqf laws in Malaysia. The findings suggest that there is room for improvement in terms of administration and governance, and the provisions of the Trustee Act of 1949 can serve as a useful reference.